In Vivo Psychopharmacological Investigation of Delphinium Denudatum and Amaranthus Spinosus Extracts on Wistar Rats - Abid, Mohammad (Basic Clin Neurosci, 2017)
INTRODUCTION: In our modern era, life style of human being changes and updates every day that may affect their health status. There is an incredible expectation that natural origin drugs lack undesirable effects not like synthetic drugs, though have the same potency and efficacy. No scientific data is available about the antianxiety properties of Delphinium denudatum root and Amaranthus spinosus leaves. In this regard, the present study was designed to carry out comparative and combined study on antianxiety properties of Delphinium denudatum root and Amaranthus spinosus leaves. METHODS: Delphinium denudatum root and Amaranthus spinosus leaves were defatted with petroleum ether, and then extracted with hydroalcoholic solvent by soxhlation process. The hydroalcoholic extract of both drugs singly and in combination were evaluated for their anxiolytic effects on Wistar albino rats in doses of 200 and 400 mg/kg using different anti-anxiety tests like Elevated Plus Maze, Staircase, Actophotometer, and Light and Dark tests. RESULTS: Both hydroalcoholic extracts possessed flavonoids, alkaloids, saponins, tannins, carbohydrates, proteins, amino acids, carbohydrates, steroids, sterols, etc. In the dose dependent manner, both the hydroalcoholic extracts produced good anxiolytic activity. The best result was obtained by a combination of them in higher dose. CONCLUSION: Hydroalcoholic extracts of Delphinium denudatum root and Amaranthus spinosus leaves and their combination may act as a potent anxiolytic agents in rats. Amaranthus spinosus was found to be more effective than Delphinium denudatum.